Transformations of students’ cognitive processes when solving PISA-like problems: A commognitive analysis - Atmaja, Satriya Adika Arif; Zaenuri; Isnarto; Dewi (Nino Adhi), Nuriana Rachmani (Jurnal Elemen, 2026)
The mathematical literacy of Indonesian students in PISA 2022 was categorized as low, highlighting the importance of understanding students’ cognitive processes in mathematical problem solving. This study examines transformations in the cognitive processes of a 15-year-old Indonesian student when solving PISA-like problems using Sfard’s commognitive framework. A qualitative approach was employed to capture detailed learning dynamics. The participant was a 15-year-old student from a randomly selected junior high school in Rembang Regency, Central Java Province, Indonesia, purposefully selected based on the mathematics teacher’s nomination for strong mathematical ability and clear evidence of cognitive shifts during problem solving. The tasks were developed by the researcher and adapted to relevant Indonesian contexts. Qualitative data—including written work, observations, and semi-structured interviews—were analyzed using mathematical literacy processes (formulating, employing, interpreting, and evaluating) and mapped onto four commognitive components: Word Use (WU), Visual Mediators (VM), Routines (R), and Narratives (N). Findings show that reflective self-evaluation supports cognitive restructuring, enabling movement from procedural errors toward coherent reasoning through shifts in WU, VM, and R. The study underscores the need for instructional designs that foster meta-level discourse, reflective thinking, and flexible visual re-representation to strengthen students’ mathematical reasoning.